The role of women in tourism activities in Kalibukbuk Tourism Village - Budi Shantika; I Gede Odi Pradika; Putu Dyah Permatha Korry (Universitas Pendidikan Nasional, 2023)
This study aimed to determine the role of women in tourism activities in the Kalibukbuk Tourism Village. The role referred to in this research was the role of women entrepreneurs in developing community-based tourism in the Kalibukbuk Tourism Village. This research was conducted in the Kalibukbuk Tourism Village, Buleleng Regency, which had become one of the Tourism Villages. Given that tourism was the main sector of economic support in the province of Bali, tourism could not be separated from the role of women as actors in existing tourism activities. Researchers asked several questions to informants, who included a number of women entrepreneurs and the Head of the Kalibukbuk Tourism Village. The selection of the informants for this research used a purposive sampling method and data validation techniques using triangulation techniques and sources. The results of this study indicated that women in the Kalibukbuk Tourism Village played a very important role in tourism activities in the village. These women entrepreneurs expedited tourism activities in the Kalibukbuk Tourism Village by providing services or goods needed by tourists, such as catering services, souvenirs, and accommodations like hotels, offering tourists a temporary residence while visiting. Directly or indirectly, this contributed to the development of tourism in the Kalibukbuk Tourism Village with the concept of community-based tourism. However, there were several obstacles to its application, such as minimal access to capital, low season, and bad weather.